Now it's personal? Learning from welfare-to-work approaches around the world (London, 2010)
"Personalisation – tailored support offered to help people (back) into work – has become a dominant feature of many welfare regimes around the world. The role of the personal adviser is an important aspect of offering more flexible, tailored support into work. While the language may differ from country to country, the challenges that many governments face, such as reducing their welfare bills and improving cost effectiveness, are similar, as is the move towards a focus on getting people into decent jobs that they then retain.